Gut Hormones and Energy Balance, The Future for Obesity Therapy? - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2009)
BACKGROUND: The prevalence of obesity is increasing in both developed and developing countries along with associated diseases such as type 2 diabetes and coronary heart disease. The recent discovery of a number of gut hormones that play a role in appetite regulation and are released or suppressed in response to a meal may offer new targets for the treatments of obesity.CONTENT: In addition to the obvious role of the gut in the digestion and absorption of nutrient, the intestine and associated visceral organs, including the pancreas, liver, and visceral adipose depots, have important sensing and signaling roles in the regulation of energy homeostatis. Signals reflecting energy stores, recent nutritional state, and other parameters are integrated in the central nervous system, particularly in the hypotalamus, to coordinate energy intake and expenditure.SUMMARY: Our understanding of the role of the gut in energy balance and insights into gut-derived signals will stimulate previously unexplored therapeutics for obesity and other disorders of energy balance.KEYWORDS: obesity, energy, balance, gut hormones, satiation, satiety